(untitled) (Hematology Meeting Reports, 2009)
n cancer patients who develop venous thromboembolism (VTE) the risk of death is more than threefold higher than in patients without cancer who have VTE1-3 and in those with cancer but no VTE.4 The high mortality rate in cancer patients with VTE is probably due to both the VTE and the fact that malignancies associated with VTE appear to follow a more aggressive course. Identifying clinical characteristics that put cancer patients with VTE at increased risk of death, either due to PE or bleeding complications, is important if their outcomes are to be improved.